Mechanistic exploration of royal jelly production in caged honey bees (Apis mellifera) - Zhi-Wei Peng; Yi-Ting Hung; Ming-Cheng Wu (Scientific Reports)
Abstract This study investigates the impact of bee pollen nutrition on the royal jelly production of honey bees (Apis mellifera). Results demonstrate that pollen diet significantly impacts hypopharyngeal gland (HPG) development and the expression of genes associated with royal jelly biosynthesis. Bees fed Brassica napus pollen exhibited superior HPG development, and increased mrjp1 expression (encoding a key royal jelly protein). While the cyp450 6AS8 gene expression (encoding a key enzyme in 10-HDA biosynthesis) was increased by pollen consumption, no distinct expression patterns were observed among the different pollen types tested. An in vitro bee cage platform for royal jelly production has been established to further understand the mechanisms behind royal jelly production in bees. The experiment demonstrated a positive correlation between the number of worker bees and the total yield of royal jelly per cage. However, when the number of worker bees is low, the amount of royal jelly each individual worker bee needs to produce increases. In conclusion, these findings enhance our understanding of the role of bee pollen nutrition in royal jelly production. Furthermore, the results from this in vitro bee cage platform suggest that the number of worker bees is a critical factor in royal jelly production, and that bees may possess a controllable mechanism for regulating royal jelly secretion.